In vitro and in vivo assessment of CYP2C9-mediated herb–herb interaction of Euphorbiae Pekinensis Radix and Glycyrrhizae Radix - Wang, Xinmin; Peng, Yunru; Jing, Xinyue; Qian, Dawei; Tang, Yuping; Duan, Jin-ao (Frontiers in Pharmacology, 2014)
According to traditional Chinese medicine theories, Euphorbiae Pekinensis Radix and Glycyrrhizae Radix shouldn’t be used together in one prescription, because their interaction leads to an unexpected consequence. However, the mechanism remains unclear. The purpose of this study was to find out whether CYP2C9 was involved in this herb-herb interaction by using tolbutamide as a probe substrate in vivo and in vitro. Both Euphorbiae Pekinensis Radix and Glycyrrhizae Radix showed induction activity toward CYP2C9, while the combination of them showed a more potent induction activity toward CYP2C9 in vivo. In vitro study revealed only the combination of the herbs could induce the activity of CYP2C9. Thus, both in vivo and in vitro study indicated combination of Glycyrrhizae Radix and Euphorbiae Pekinensis Radix could induce the activity of CYP2C9 to a high level, which may result in decreased plasma levels of major active ingredients of these two herbs, as well as other herbs in the prescriptions. Further research also appears to be necessary to identify the main enzymes involved in the metabolism of the active ingredients in Glycyrrhizae Radix and Euphorbiae Pekinensis Radix.